Pragmatic Approach to Language Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the places of use of language units in speech, the importance of pragmatic tools in discourse. Also, phenomena related to the speech act, speech situation, speaker personality, which are the central concepts of linguistic pragmatics, are analyzed on the basis of examples.